Setting the Record Straight : Essays on Ecclesiology, Missiology and Evangelism - Longwe, Hany (Book collections on Project MUSE., 2021)
" 'Kusadziwa Nkufa Komwe' (Lack of Knowledge is as Being Dead) is a Nyanja maxim, African Philosophy that is true the world over. A person who lacks knowledge is as good as dead, inactive and insensitive. A dead person does not contribute to good life. Lack of knowledge leads to destruction, but having knowledge leads to informed decisions and freedom. Setting the Record Straight is about correction wrong understanding and replacing it with liberating knowledge, to the benefit of both church and society."--Publisher.